Integrative physiological, metabolomic, and transcriptomic insights into strawberry adaptation to boron deficiency stress - Guo, Xiaoyu (Plant physiology and biochemistry : PPB, 2025)
Copyright © 2025 Elsevier Masson SAS. All rights reserved.